1995
DOI: 10.1177/019394599501700306
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Intuitive Nurses

Abstract: A description is provided of the process used to verify characteristics of intuitive nurses that had been reported in the literature. These characteristics supplied the framework for construction of the Miller Intuitiveness Instrument (MII) reported earlier (Miller, 1993). Evidence for validity of the MII was provided in the Miller (1993) study by examining factor analyses and correlations with the intuitive component of the Myers-Briggs Type Indicator (MBTI). The following characteristics were subsequently ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 8 publications
2
24
0
1
Order By: Relevance
“…7 In Kosowski and Roberts' study, the participants spoke about the importance of having an accurate and substantive knowledge of contextual variables because acting on their intuition felt like taking a risk, and agreed that comprehensive knowledge of the agency's system and its adherence to protocols was a key factor in their ability to use intuition in clinical decision making. 4 Miller (1995), also mentioned clinical mastery to describe an intuitive nurse. 2 The results of confirmed that expertise in intuitive nurses would be achieved through three phases; cognitive intuition, where assessment is processed subconsciously and can be rationalized in hindsight; transitional intuition, where a physical sensation and other behaviors enter the nurse's awareness; and embodied intuition, when the nurse trusts the intuitive thoughts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7 In Kosowski and Roberts' study, the participants spoke about the importance of having an accurate and substantive knowledge of contextual variables because acting on their intuition felt like taking a risk, and agreed that comprehensive knowledge of the agency's system and its adherence to protocols was a key factor in their ability to use intuition in clinical decision making. 4 Miller (1995), also mentioned clinical mastery to describe an intuitive nurse. 2 The results of confirmed that expertise in intuitive nurses would be achieved through three phases; cognitive intuition, where assessment is processed subconsciously and can be rationalized in hindsight; transitional intuition, where a physical sensation and other behaviors enter the nurse's awareness; and embodied intuition, when the nurse trusts the intuitive thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…4 Miller (1995), also mentioned clinical mastery to describe an intuitive nurse. 2 The results of confirmed that expertise in intuitive nurses would be achieved through three phases; cognitive intuition, where assessment is processed subconsciously and can be rationalized in hindsight; transitional intuition, where a physical sensation and other behaviors enter the nurse's awareness; and embodied intuition, when the nurse trusts the intuitive thoughts. 12 However, in the opinion of Pretz and Folse, the experience has effect on just some special parts of intuition, such as skillful domain, even though there are no correlations between them in terms of physical and spiritual extents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations